Combinatorial Analysis of Lean Manufacturing and Reverse Engineering For Joint Propeller Shaft in Automobile Industry A Review - Manish Deshmukh; Anshul Gangele; Deepak Kumar Gope (AG Volumes, 2021)
A wheel’s axle is its middle shaft. Axles keep the wheels in place in relation to one another and to the vehicle’s frame. Attempts are being made to address this problem in this publication. A comprehensive review of the relevant literature is now being conducted, and several potential study avenues have been identified. Lean Manufacturing is a fast-growing and efficient strategy in today’s competitive marketplace. Lean Production is used to continually remove wastes from the manufacturing process in order to increase productivity and efficiency. It is the primary goal of lean manufacturing to meet the needs of the customer in terms of quality and cost. In addition to identifying the root causes of waste, the method helps to remove it by establishing clear rules and norms. This article focuses on the fundamentals of lean manufacturing in order to increase production, quality, and decrease the product’s cost. Various wastes have been classified. The methods for reducing waste are explored in detail.